2020
DOI: 10.1016/j.ejso.2020.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Patients with colorectal peritoneal metastases and high peritoneal cancer index may benefit from cytoreductive surgery and hyperthermic intraperitoneal chemotherapy

Abstract: Background: Peritoneal cancer index (PCI) >20 is often seen as a contraindication for cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with peritoneal metastases (PM) from colorectal cancer. The aim of this study was to compare the overall survival in colorectal PM patients with PCI >20 and PCI 20 treated with CRS and HIPEC to those having open-close/ debulking procedure only. Methods: All patients with colorectal PM and intention to treat with CRS and HIPEC in Upps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“… 292 , 293 , 294 , 295 For example, palliative surgery for patients with intraperitoneal metastases such as liver cancer and ovarian cancer can alleviate their symptoms and improve their quality of life. 296 , 297 …”
Section: Interventions For Tumor Metastasismentioning
confidence: 99%
“… 292 , 293 , 294 , 295 For example, palliative surgery for patients with intraperitoneal metastases such as liver cancer and ovarian cancer can alleviate their symptoms and improve their quality of life. 296 , 297 …”
Section: Interventions For Tumor Metastasismentioning
confidence: 99%
“…On the other hand, there are a few series such as the one published by Birgisson et al. that demonstrated that despite worse OS in high PCI, there is still a survival advantage in patients undergoing CRS/HIPEC with median OS of 20 months and 7% surviving beyond 5 years 14 In our series, we demonstrated increased operative times, EBL, and increased overall complications rates; nonetheless, the rate of major complications, transfusions, reoperations, ICU and hospital LOS were similar. We have demonstrated that in an experienced, high‐volume, tertiary referral center CRS/HIPEC in the high PCI population can be accomplished with acceptable morbidity.…”
Section: Discussionmentioning
confidence: 99%
“… 36 It is not possible to define an absolute cut-off value above which CRS and HIPEC should not be performed, since long-term survival in selected cases with high PCI values is sometimes possible. 37 Nevertheless, global experts agree that surgical treatment should only be performed if complete macroscopic cytoreduction is achievable. 38 This general opinion is based upon the strongly diminished survival of patients with incomplete macroscopic cytoreduction.…”
Section: Extent Of Peritoneal Diseasementioning
confidence: 99%